TANGGUNG JAWAB PPAT TERHADAP AKTA JUAL BELI YANG DIBUAT TANPA SEPENGETAHUAN ISTRI SAH DARI SALAH SATU PENGHADAP (STUDI KASUS PENGADILAN NEGERI SERANG NOMOR 39/PDT.G/2017/PN SRG JUNCTO PUTUSAN PENGADILAN TINGGI BANTEN NOMOR 60/PDT/2018/PT BTN JUNCTO PUTUSAN MAHKAMAH AGUNG NOMOR 227 K/PDT/2019) - Natasya Elvara Yusuf; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2021)
The sale and purchase transaction i carried out with the Sale and Purchase Deed Number made by PPAT without the knowledge and approval of the seller's wife who in making the AJB the seller gives the selling power to the buyer so that only the buyer faces PPAT, in which it turns out that the seller uses a false identity and is not married and the object of land being sold is a joint property. The problem in writing this thesis is how the PPAT is responsible for the deed of sale made without the knowledge of the legal wife of one of the parties and what are the legal consequences for the status of the land being traded using the deed of sale made by PPAT without the knowledge of the legal wife of one of the parties. facing. The research method is normative legal research. The results of the research in this thesis indicate that the PPAT against the deed he made without the knowledge and approval of the wife is illegitimate and null and void can be held accountable administratively, civilly but not criminally because it is not proven. Regarding the legal consequences of the land status which AJB canceled by law, the land status should be returned to its original state by filing a lawsuit to the State Administrative Court